2009
DOI: 10.1002/joc.1855
|View full text |Cite
|
Sign up to set email alerts
|

Trend patterns in global sea surface temperature

Abstract: Isolating long-term trend in sea surface temperature (SST) from El Niño southern oscillation (ENSO) variability is fundamental for climate studies. In the present study, trend-empirical orthogonal function (EOF) analysis, a robust space-time method for extracting trend patterns, is applied to isolate low-frequency variability from time series of SST anomalies for the 1982-2006 period. The first derived trend pattern reflects a systematic decrease in SST during the 25-year period in the equatorial Pacific and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 20 publications
0
20
0
2
Order By: Relevance
“…The striking feature of the method is its ability to systematically extract the trend patterns, albeit small. Application to the global sea surface temperature (SST) data showed that trend EOF analysis has advantages at capturing trend rather than maximum variance patterns over the usual EOF analysis (Barbosa and Andersen 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The striking feature of the method is its ability to systematically extract the trend patterns, albeit small. Application to the global sea surface temperature (SST) data showed that trend EOF analysis has advantages at capturing trend rather than maximum variance patterns over the usual EOF analysis (Barbosa and Andersen 2009). …”
Section: Introductionmentioning
confidence: 99%
“…In particular, when considering low-frequency variability, traditional EOF analysis may encounter technical difficulties: although a trend pattern may be physically relevant, it may not explain a large fraction of variance. As a consequence, the trend signal is often split into different modes (Hannachi 2007; Barbosa and Andersen 2009). To eliminate the aforementioned limitation of conventional EOF analysis, a novel method named trend EOF analysis was suggested by Hannachi (2007) by means of looking for a nonlinear, rank-based modification to the usual EOF analysis.…”
Section: Introductionmentioning
confidence: 99%
“…A multivariate trend analysis based on the empirical orthogonal function (hereinafter TEOFA) of ranked anomalies was recently proposed by Hannachi (2007) to perform such a decomposition. Compared to the conventional covariance-based EOF analysis, the superiority of TEOFA in isolating the low-frequency ENSO signal from the long-term trend of global sea surface temperature was recently demonstrated by Barbosa and Andersen (2009). This current study aims at applying this new methodology to the DTR data in Taiwan to detect multiple trends and at examining their teleconnectivity to large-scale circulations in order to answer the aforementioned questions.…”
Section: Introductionmentioning
confidence: 99%
“…Trend extraction is an important topic in climate research (see Hannachi 2007;Barbosa and Andersen 2009;Li et al 2011). Climate scientists perform RTA to study how the trend component M(t) changes over time.…”
Section: Resultsmentioning
confidence: 99%